Back Cover: Synthesis and Reactivity of Fluoroalkyl Copper Complexes by the Oxycupration of Tetrafluoroethylene (Angew. Chem. Int. Ed. 39/2017). Issue 39 (9th August 2017) - Ohashi, Masato; Adachi, Takuya; Ishida, Naoyoshi; Kikushima, Kotaro; Ogoshi, Sensuke
Abstract : Copper(I)‐mediated generation of −OCF2 CF2 − moieties through the oxycupration of tetrafluoroethylene using either copper aryloxides or alkoxides is described by S. Ogoshi et al. onpage 11911 ff. The key intermediates, 2‐aryloxy‐ and 2‐alkyloxy‐1, 1, 2, 2‐tetrafluoroethyl copper complexes, were obtained and subsequently reacted with aryl iodides to afford ROCF2 CF2 Ar (R=aryl or alkyl) in high yields.